Carbon emission from Western Siberian inland waters - Karlsson, Jan; Serikova, Svetlana; Vorobyev, Sergey N. (биолог); Rocher-Ros, Gerard; Denfeld, Blaize; Pokrovsky, Oleg S. (Nature Communications, 2021)
High-latitude regions play a key role in the carbon (C) cycle and climate system. An important question is the degree of mobilization and atmospheric release of vast soil C stocks, partly stored in permafrost, with amplified warming of these regions. A fraction of this C is exported to inland waters and emitted to the atmosphere, yet these losses are poorly constrained and seldom accounted for in assessments of high-latitude C balances. This is particularly relevant for Western Siberia, with its extensive peatland C stocks, which can be strongly sensitive to the ongoing changes in climate. Here we quantify C emission from inland waters, including the Ob’ River (Arctic’s largest watershed), across all permafrost zones of Western Siberia. We show that the inland water C emission is high (0.08–0.10 Pg C yr−1) and of major significance in the regional C cycle, largely exceeding (7–9 times) C export to the Arctic Ocean and reaching nearly half (35–50%) of the region’s land C uptake. This important role of C emission from inland waters highlights the need for coupled land–water studies to understand the contemporary C cycle and its response to warming.